Relationships between the Visual Evaluation of Soil Structure (VESS) and soil properties in agriculture: A meta-analysis (Scientia Agropecuaria, 2023)
The objective of this study was to analyze the relationships between the Visual Evaluation of Soil Structure (VESS) and soil properties that make its adoption widely used in agriculture. For this, 25 papers related to the VESS (2009-2022) were considered where the information of the authors, the soil property: bulk density (BD), total soil porosity (TP), soil penetration resistance (PR), macroporosity, microporosity, soil organic carbon (SOC), and mean weight diameter of stable aggregates (MWD). The sample size (n=120 cases), and the correlation coefficient were extracted. To measure this relationship, the correlation coefficient of all studies was contemplated. A meta-analysis was carried out to obtain a global measure of the correlation between the VESS and soil properties across the studies. In the first instance, a fixed effects model was fitted for the correlation (effect size, known as the response variable in the meta-analysis). Subsequently, a random effects model was fitted for the correlation, followed by a subgroup analysis according to soil properties, due to the presence of high heterogeneity between studies. The overall effect (average correlation coefficient) of the fitted random effects model was 0.31 with a confidence interval (CI) of [0.22;0.41]. The heterogeneity between studies was high ( =94.0%) and statistically significant p
Keywords: soil structure; bulk density; total soil porosity; soil penetration resistance; random effect models; forest plot